The Use of English Double Prepositions in English as a Second Language (ESL) Nursing Students - Bello Muhammad Jajere (Journal of English as A Foreign Language Teaching and Research, 2025)
This study examines the use of English prepositions among students of Shehu Sule College of Nursing and Midwifery (SSCNM), Damaturu, with a focus on double prepositions. The goal of this study is to identify common errors, classify error types, determine the most problematic prepositions, analyze underlying causes, and propose instructional solutions. Data were collected from 92 students through questionnaires and essay tasks requiring the insertion of appropriate prepositions in given contexts. The responses were analyzed using descriptive statistics. Findings indicate that spatial and directional prepositions posed significant challenges, with “Above” having the highest error rate (39.7%), followed by “Onto” (25.9%) and “Toward” (22.4%). The occurrence of errors involving “Within” and “Into” were lower (5.2% each), while “Without” had the least occurrence (1.7%). This study attributes these difficulties to inadequate exposure to authentic language use, first language interference, and insufficient explicit instruction. To mitigate these challenges, it recommends contrastive analysis in teaching, where English prepositions are compared with their equivalents in students’ native languages. Task-based learning should be integrated into nursing scenarios to reinforce contextual understanding. In addition, error analysis workshops should be held to help students identify and correct common prepositional errors. Exposure to authentic English materials, such as medical texts and recorded professional conversations, is also encouraged to enhance practical use. Implementing these strategies can improve students’ prepositional competence and overall English proficiency. ns, analyze underlying causes, and propose instructional solutions. Data were collected from 92 students through questionnaires and essay tasks requiring the insertion of appropriate prepositions in given contexts. The responses were analyzed using descriptive statistics. Findings indicate that spatial and directional prepositions posed significant challenges, with “Above” having the highest error rate (39.7%), followed by “Onto” (25.9%) and “Towards” (22.4%). Errors involving “Within” and “Into” were lower (5.2% each), while “Without” had the least occurrences (1.7%). The study attributes these difficulties to inadequate exposure to authentic language use, first language interference, and insufficient explicit instruction. To mitigate these challenges, it recommends contrastive analysis in teaching, where English prepositions are compared with their equivalents in students’ native languages. Task-based learning should be integrated into real-life nursing scenarios to reinforce contextual understanding. Additionally, error analysis workshops should be conducted to help students identify and correct common prepositional errors. Exposure to authentic English materials, such as medical texts and recorded professional conversations, is also encouraged to enhance practical usage. Implementing these strategies can improve students’ prepositional competence and overall English proficiency.